2019
DOI: 10.3390/atmos10100564
|View full text |Cite
|
Sign up to set email alerts
|

A Wind Tunnel Study on the Correlation between Urban Space Quantification and Pedestrian–Level Ventilation

Abstract: Correlation research on urban space and pedestrian–level wind (PLW) environments is helpful for improving the wind comfort in complex urban space. It could also be significant for building and urban design. Correlation research is usually carried out in a space with clear urban spatial characteristics, so it is necessary to define the space first. In this paper, a typical urban area in Nanjing, China, is selected as the research object, and a spatial partition method is used to divide the real complex urban sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Urban ventilation research has significance for urban planning [ 39 , 40 ]. Traditional urban planning lacks the aspect of climate research, which plays an important role in the realization of urban sustainable development and in solving urban environmental problems.…”
Section: Discussionmentioning
confidence: 99%
“…Urban ventilation research has significance for urban planning [ 39 , 40 ]. Traditional urban planning lacks the aspect of climate research, which plays an important role in the realization of urban sustainable development and in solving urban environmental problems.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1960s, studies of pedestrian wind environments have attracted significant attention. Relevant studies were generally categorized into three aspects, one that examines the effects of a single high-rise building on its surrounding pedestrian-level wind field [1][2][3][4][5], another that investigates the effects of high-rise buildings [6][7][8][9][10][11][12][13][14] and another that focuses on urban street canyons [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This finding contradicts results obtained from previous studies on parallel street canyon passages. Li et al [12] validated the wind network index based on wind tunnel test results (spatial average velocity, surface pressure on individual buildings and total drag force). They found that the wind network index can effectively identify building layout effects on the wind field.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers focus on urban wind field construction and analysis. The straightforward methods are wind tunnel testing and field measurements [2][3][4][5]. Earlier wind tunnel tests were done by Wiren et al [2], where they conducted experimental studies of wind velocities in passages between and through block-type building models with various types of layouts.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Weerasuriya et al [4] conducted wind tunnel studies to uncover the effects of twisted wind flows on pedestrian-level wind fields in an urban environment. Finally, Li et al performed wind tunnel studies and tried to find the correlation between urban space quantification and pedestrian-level ventilation [5].…”
Section: Introductionmentioning
confidence: 99%